Facilitating action planning within audit and feedback interventions: a mixed-methods process evaluation of an action implementation toolbox in intensive care - Gude, Wouter T.; Roos-Blom, Marie-José; van der Veer, Sabine N.; Dongelmans, Dave A.; de Jonge, Evert; Peek, Niels; de Keizer, Nicolette F. (Implementation science : IS, 2019)
Background Audit and feedback (A&F) is more effective if it facilitates action planning, but little is known about how best to do this. We developed an electronic A&F intervention with an action implementation toolbox to improve pain management in intensive care units (ICUs); the toolbox contained suggested actions for improvement. A head-to-head randomised trial demonstrated that the toolbox moderately increased the intervention’s effectiveness when compared with A&F only. Objective To understand the mechanisms through which A&F with action implementation toolbox facilitates action planning by ICUs to increase A&F effectiveness. Methods We extracted all individual actions from action plans developed by ICUs that received A&F with ( n = 10) and without ( n = 11) toolbox for 6 months and classified them using Clinical Performance Feedback Intervention Theory. We held semi-structured interviews with participants during the trial. We compared the number and type of planned and completed actions between study groups and explored barriers and facilitators to effective action planning. Results ICUs with toolbox planned more actions directly aimed at improving practice ( p = 0.037) and targeted a wider range of practice determinants compared to ICUs without toolbox. ICUs with toolbox also completed more actions during the study period, but not significantly ( p = 0.142). ICUs without toolbox reported more difficulties in identifying what actions they could take. Regardless of the toolbox, all ICUs still experienced barriers relating to the feedback (low controllability, accuracy) and organisational context (competing priorities, resources, cost). Conclusions The toolbox helped health professionals to broaden their mindset about actions they could take to change clinical practice. Without the toolbox, professionals tended to focus more on feedback verification and exploring solutions without developing intentions for actual change. All feedback recipients experienced organisational barriers that inhibited eventual completion of actions. Trial registration ClinicalTrials.gov, NCT02922101 . Registered on 26 September 2016.